Cante lá que eu canto cá: poéticas populares dentro e fora da moldura - Bruna Paiva de Lucena (Estudos de Literatura Brasileira Contemporânea)
This article makes an investigation on the Biblioteca de Cordel Collection, from the publishing house Hedra, going through the discussion on the publishing of cordel as a leaflet, and the importance of typographical establishments in Northeast Brazil in this process. We analyze also the publishing of this kind of poetry as books, as well as the prefaces written by renowned intellectuals as a means of legitimizing this literary production, considering the study of the relations between popular poetics and the intellectual perspective.